Seven tips for clinical supervision in the time of COVID 19 - Schultz, Karen; Singer, Alexander; Oadansan, Ivy (Canadian Medical Education Journal, 2020)
Virtual care (VC) rapidly has become the preferred care model in family medicine settings during the COVID-19 pandemic. Both residents and preceptors must rapidly adapt and develop new skills to provide and supervise virtual care. The College of Family Physicians of Canada (CFPC) created a VC supervision guide for family medicine residents and preceptors by quickly mobilizing a consensus driven approach leveraging existing CFPC educational committees, representing a broad range of teachers and residents in the country. The guide can be adapted to other settings and is provided in the hopes of being helpful to all preceptors providing VC and (virtual) supervision during the pandemic.